Penegakan Hukum terhadap Pelaku Pembukaan Lahan yang Menyebabkan Kebakaran Hutan - Ratu Sheebakayla (Savana, 2024)
Abstract Forest fires caused by land clearing activities are a serious problem that threatens the ecosystem, public health, and the economy. Pollution and environmental damage in forest fire cases in Indonesia are serious problems. The purpose of this study was to determine and analyze the regulation and implementation of law enforcement against perpetrators of land clearing that cause forest fires. The research method used is normative juridical. The legal materials used are laws and regulations related to the environment and court decisions 205 / Pid.B / LH / 2023 / PN Kgn. The results of the study are that law enforcement can be used as a rule to overcome environmental problems by referring to the Law on Environmental Management and Protection, the Law on Plantations, the Law on Prevention and Eradication of Forest Destruction. The law enforcement carried out is to impose a criminal sentence on the perpetrators to imprisonment for 10 (ten) months and a fine of IDR 30,000,000.00 (thirty million rupiah). Conclusion: The Indonesian Government continues to strengthen regulations and law enforcement to address this issue, although major challenges remain regarding law enforcement in the field and compliance of perpetrators with existing regulations. Suggestions include strengthening regulations and strict law enforcement, educating the public about the dangers of forest fires, and developing firefighting infrastructure. Collaboration between stakeholders is also important in this effort. It requires commitment to handling and preventing forest fires and also requires participation from all parties to continue to protect and preserve Indonesia's forests, in order to become useful provisions for future generations